A rare case of pre-hospital globe enucleation after a penetrating injury to the orbit during an assault: A case report and literature review. (2020) - Elkbuli, Adel; Meneses, Evander; Kinslow, Kyle; McKenney, Mark; Boneva, Dessy
Highlights: This is a rare case of traumatic enucleation of the right globe sustained after an assault. Traumatic enucleation requires significant retro-ocular force to cause globe separation from the surrounding supportive structures within the orbit. Optic nerve avulsion from traumatic enucleation can cause contralateral visual deficits such as temporal hemianopia in the uninjured eye. Current open and closed globe injury classification systems are not applicable to traumatic enucleation indicating the need for new system development to guide treatment options. Abstract: Introduction: Ocular trauma is a common occurrence in trauma settings but often occurs with little to no effect on the vision of the patient. Traumatic enucleation is a rare but devastating injury. Case presentation: A 40-year-old male presented to our trauma center after an assault resulting in right globe enucleation. CT confirmed absence of the globe with disruption of the ipsilateral orbital contents and distal optic nerve disruption. The patient was started on intravenous antibiotics and the right orbit was packed. He was taken to the operating room for exploration of the right orbit and placement of an implant. His remaining hospital course was unremarkable. Discussion: Documented mechanisms of injury for traumatic enucleation are diverse, but often involve significant retro-ocular force to completely dislodge the globe from the orbit. Optic nerve avulsion may cause associated optic nerve chiasm damage leading to temporal hemianopia in the uninjured contralateral eye. Treatment involves stabilization and preparation for future implant placement. Conclusion: Traumatic enucleation is extremely rare. Development of a grading system applicable to traumatic enucleation may be helpful in guiding management in this complex patient population.